Bibliometric Analysis of Research on ESG - Król, Patryk Janusz; Jędrzejewski, Piotr (Journal of Finance and Financial Law, 2025)
The purpose of the article. The aim of this article is to provide a comprehensive bibliometric analysis of the academic literature on Environmental, Social, and Governance (ESG) topics within the domains of economics, business, and finance. By examining 4,499 documents indexed in the Web of Science (WoS) database from 2006 to 2024, the study aims to identify key trends, research clusters, influential publications, and knowledge gaps in ESG-related research. Methodology. The methodology involves the use of the Bibliometrix package and its graphical interface Biblioshiny, which enabled advanced science mapping techniques, including co-citation, co-authorship, and keyword co-occurrence analyses. Data were filtered based on relevant WoS categories, and analytical metrics included publication growth rates, citation statistics, authorship patterns, and thematic clustering. Results of the research. The results reveal a rapidly growing interest in ESG, with an annual publication growth rate of 38.83% and an increasing focus on topics such as corporate performance, cost efficiency, disclosure practices, and governance structures. Four major thematic clusters were identified: ESG disclosure and firm performance, CSR and sustainability, corporate financial management, and emerging markets. The analysis highlights a growing integration of ESG into investment strategies and corporate governance, though the causal mechanisms linking ESG performance to financial outcomes remain insufficiently explained. The study concludes that ESG has evolved into a multidimensional and strategic framework, surpassing CSR in conceptual precision and regulatory relevance.